Integritas Akademik: Prediktor Kesejahteraan Siswa di Sekolah - Ramdani, Zulmi; Prakoso, Bagus Hary (Pusat Asesmen dan Pembelajaran, 2019)
Student’s school well-being is one of the factors that determine the extent to which the quality of education can be felt effectively by all individuals in it. The concept of wellbeing arises because of the overall collaboration and mutual support among the elements of education in schools. One of the factors that contribute to the student’s school wellbeing is academic integrity. Academic integrity refers to the tendency of students to behave as the values of truth that they believe in and in accordance with the demands of the environment. This study aims to examine the influence and contribution of academic integrity to the well-being of students at school. The quantitative research design by testing of regression assumptions was carried out in this study. The subjects involved in this study amounted to 186 participants by being selected based on the random sampling method. The results of the study indicate that academic integrity moderately influences the well-being of students at school. This assumes that personal factors such as academic integrity are needed to support the quality of effective learning, because learning outcomes depend on how the mental and psychological conditions of the students themselves.Abstrak Kesejahteraan siswa di sekolah menjadi salah satu faktor yang menentukan sejauhmana kualitas pendidikan itu bisa dirasakan efektif oleh seluruh individu yang ada di dalamnya. Kesejahteraan muncul karena adanya kolaborasi yang menyeluruh dan saling mendukung di antara elemen pendidikan di sekolah. Salah satu faktor yang ikut berperan terhadap kesejahteraan siswa di sekolah adalah integritas akademik. Integritas akademik mengacu kepada kecenderungan siswa untuk bersikap dan bertingkah laku sebagaimana nilai kebenaran yang mereka yakini dan sesuai dengan tuntutan lingkungan. Penelitian ini bertujuan untuk menguji pengaruh dan kontribusi integritas akademik terhadap kesejahteraan siswa di sekolah. Desain penelitian kuantitatif dengan pengujian asumsi regresi dilakukan dalam penelitian ini. Subjek yang terlibat dalam penelitian berjumlah 186 partisipan dengan dipilih berdasarkan metode random sampling. Hasil penelitian menunjukkan bahwa integritas akademik secara moderat mempengaruhi kesejahteraan siswa di sekolah. Hal ini mengasumsikan bahwa faktor personal seperti integritas akademik dibutuhkan dalam menunjang kualitas pembelajaran yang efektif, karena hasil belajar itu tergantung pada bagaimana kondisi mental dan psikologis siswa itu sendiri